Mesostigmata diversity by manure type: a reference study and new datasets from southwestern Iran - Sara Farahi; Parviz Shishehbor; Alireza Nemati; M. Alejandra Perotti (Experimental and Applied Acarology, 2022)
Manure-inhabiting Mesostigmata mites are important biological control agents of pest flies. However, the biodiversity of this mite community is mainly known from Europe and America, and especially from cattle manure. This study examined the diversity and abundance of Mesostigmata mites associated with various types of manure in an (intensive) agricultural region of the Middle East, i.e., the city Ahvaz and its suburbs, in southwest Iran. Mite samples were extracted from manure of cattle, buffalo, sheep, horse, poultry and quail in 30 livestock and poultry farms. In total, 40 species belonging to 24 genera and 16 families were identified. The most diverse families were Laelapidae with eight species, Macrochelidae with seven and Parasitidae with six. Macrocheles muscaedomesticae and Uroobovella marginata were the most widespread species, recorded in 28 and 27 out of 30 collection sites, respectively. Two species, M. sumbaensis and U. marginata , were found in all studied manures. Simpson’s diversity index recorded the highest diversity in buffalo and sheep manure. Real and theoretical species richness (rarefaction curves) were congruent in number of individuals. The presence of seven species of Macrochelidae in the manure confirms that these are important predators of the house fly for the region of Ahvaz and its suburbs. Members of the Parasitidae were highly prevalent, with one species known as a specialized predator of house fly eggs. This work aims to encourage further studies on the diversity of Mesostigmata in these agricultural settings, and further continue assessing the feasibility of these mites as effective biocontrol agents of filth flies in different types of manure and from different corners of the world.